CONFLICT OF LAWS IN MALAYSIAN PLURALISTIC SOCIETY: AN EXAMPLE OF ANTINOMY OF LAW IN A DUAL SYSTEM - Ahmad, Rusniah (Journal Sampurasun : Interdisciplinary Studies for Cultural Heritage, 2017)
Malaysia has a complex legal history with a multiracial society in place after the end of British colonization. Its multi-religious presence is another reflection provided in Article 3 of the Malaysian Federal Constitution, “Islam is the religion of the Federation, but other religions may be practiced in peace and harmony in any part of the Federation”. The legal system is clearly expressed in its adoption of the constitutional supremacy doctrine and the existence of the three main branches of government with a federal system of government. In so far as family law is concerned the legal system has accommodated this form by acknowledging the unwritten sources of customary laws of the various ethnic communities. However, this accommodation to realized freedom of religion has resulted in a dual system of Family Law. A set of laws and courts for the Muslims and another for the non-Muslims. It was believed that this will not be problematic since the arrangement catered for the rights of all. As Malaysian society become intertwined this arrangement may not be so easy after all. The dual family law has caused conflicting issues to arise especially in divorce proceedings and child custody battles for couples of different ethnic (and religious) groups. This is an antinomy in a pluralistic society with a dual legal system. The values that have been developed and accepted are instill among Malaysians that everyone has the right to enjoy fundamental liberties and freedom afforded by the Federal Constitution and respect is given to all to choose their own faiths and way of life in accordance with the law. This is a challenge not only for the government authorities but to the legal fraternities and judiciary in deriving acceptance and conformity on the legal compliance of all parties concerned.